FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU MASYARAKAT DALAM PENCEGAHAN COVID-19 - Safrina Edayani; Rita Zahara; Nurul Fadhilah (Sekolah Tinggi Ilmu Kesehatan Muhammadiyah Lhokseumawe, 2022)
Public awareness of prevention at the individual level is also still low. There are still many people who neglect to wash their hands using soap and clean running water. Even many of them after leaving the house without washing their hands properly. The purpose of the study was to determine the relationship between age, education and knowledge with community behavior in preventing Covid-19. The design of this research is analytic, with a cross sectional approach. The population in this study is the entire community, amounting to 225 people. The number of samples as many as 69 respondents was determined by using accidental sampling technique. This research was conducted on July 12 to July 17, 2021. The analysis was carried out using a computerized process through the chi-square test. Based on the results of the study, it was found that the age group was in the 26-45 year category by 39.1%. Education is in the middle category of 42.1%. Public knowledge about Covid-19 prevention is in the high category of 43.5%. Community behavior in preventing Covid-1 is in the good category at 58.0%. The results of the p-value < = 0.05, this proves that there is a relationship between age, education and knowledge with community behavior in preventing Covid-19.